Pembuatan Rangka Sepeda Karbon Epoxy Komposit Dengan Modifikasi Teknik Lay-Up Pada Metode Laminasi Basah - Deva Muhammad Sachio; Carolus Bintoro (Politeknik Negeri Bengkalis, 2021)
In this day, composites has been widely used. Composites are used to reduce weight and increase the strength of the bicycle frame while minimizing costs. This is because composites are known as strong and lightweight materials. Apart from that, the costs incurred when making composites are much cheaper than using aluminum alloy material to make bicycles. One type of composite that is suitable for use in problems that exist in bicycle frames is composite carbon fibre combined with epoxy resin. Therefore, in this final project the author will make a bicycle frame using a composite material with a combination of fibre in the form of carbon fibre and a matrix in the form of epoxy resin. In the manufacturing process, the author also made modifications to the technique of making the bicycle frame. The method used is the wet lamination method, while the modification made is the process where the wet lamination is carried out in the direction of the rolled fibre. In the end, identification will be carried out by comparing the bicycle frame made with carbon composite material and the conventional bicycle frame made with aluminum alloy material. Keywords : Bicycle Frame, Carbon Composite, Wet Lamination Method